Clinical findings and outcome predictors for multinodular pulmonary fibrosis in horses: 46 cases (2009‐2019) - Amanda Craven; Amy Todd‐Donato; Tracy Stokol; Rachel Liepman; Ilana Glasberg; Pamela Wilkins; Daniela Luethy; David Wong; Angelika Schoster; Astrid J. van denBrom ‐ Spierenburg; Joy E. Tomlinson (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Prognostic indicators for equine multinodular pulmonary fibrosis (EMPF), an interstitial fibrosing lung disease, are poorly described. Hypothesis/Objectives Describe diagnostic findings and outcome predictors for EMPF. Animals Forty‐six adult horses with EMPF. Methods Retrospective multicenter case series from 2009 to 2019. Radiographic (n = 27) and ultrasonographic studies (n = 19) from EMPF horses and bronchoalveolar lavage fluid (BALF) cytology from 6 EMPF and 13 asthma cases were independently reviewed and blinded to diagnosis and outcome. Associations between predictor variables and survival were assessed by predictor screening followed by Fisher's exact and Wilcoxon rank sum tests. Results Primary clinical findings were weight loss (36/46, 78%), increased respiratory effort (33/46, 72%), tachypnea (32/46, 70%), and fever (18/46, 39%). Macrophage atypia was seen in more EMPF than asthmatic horse BALF (67% vs. 8%; P = .02). Equine herpesvirus 5 (EHV‐5) was detected in 24 of 30 (80%) and hyperfibrinogenemia in 25 of 28 (89%) cases. Twenty‐seven of 46 horses (59%) and 11 of 45 (24%) survived to discharge and to 3 months, respectively. Three‐month survival was associated with lower median (range) respiratory rates (30 [24‐36] vs. 41 [30‐60] breaths per minute; P = .04), and higher BALF lymphocyte:neutrophil ratios (4.7 [1.4‐22] vs. 0.47 [0.11‐1.9]; P = .01) and blood lymphocyte counts (1.25 [0.93‐2.55] vs. 0.90 [0.70‐1.24] × 109/L; P = .03). Imaging findings, EHV‐5 detection, and corticosteroid treatment were not associated with survival. Conclusions and Clinical Importance Fever is not a sensitive clinical sign of EMPF. Diagnostic testing should be pursued for horses with increased respiratory rate and effort and weight loss. The prognosis for EMPF horses is poor. Corticosteroid treatment does not improve 3‐month survival.